Light Distribution Patterns in Microresonator Chain PICs with Kerr-Nonlinearity - Ghosh, Alekhya; Pal, Arghadeep; Hill, Lewis; Campbell, Graeme N.; Bi, Toby; Zhang, Yaojing; Alabbadi, Abdullah; Zhang, Shuangyou; Del'Haye, Pascal (British and Irish Conference on Optics and Photonics, BICOP 2024 in Proceedings British and Irish Conference on Optics and Photonics 2024, 2024)
We demonstrate control of optical power patterns in one-dimensional photonic lattices of coupled resonator optical waveguides (CROWS) induced by the Kerr effect. This can advance photonic integrated circuits, especially for light steering and optical computing.
CRIS-Team Scopus Importer:2025-04-01